Collagen prolyl 4-hydroxylase subunit α member-induced head and neck squamous cell carcinoma aggressiveness is antagonized by LLGL2 via reduced expression of occludin - Xu Miao; Shi Run; Yang Jie; Chen Heng; Liu Shihua; Yu Shupei; Li Sasa; He Wenqiang; Sy Man-Sun; Lu Mingjian; Zhang Huixia; Li Chaoyang (Acta Biochimica et Biophysica Sinica)
There are three isoforms of human collagen prolyl 4-hydroxylases (C-P4Hs), each of which has been reported to play an important role in regulating the progression of a variety of human cancers. By analyzing TGCA datasets on human head and neck squamous cell carcinoma (HNSC), we find that a higher expression of all three C-P4HAs (the α subunit of C-P4Hs) is a superior prognostic indicator than a higher expression of two or a single C-P4HA. Unexpectedly, some patients with higher levels of three C-P4HAs survive longer than patients whose tumors have lower expression of C-P4HAs. Therefore, there may be molecule(s) that can negate the deleterious effects of overexpressing C-P4HAs during cancer progression. By constructing a functional protein interaction network of C-P4HAs and analyzing molecules whose expressions are correlated significantly with that of C-P4HAs, we identify scribble cell polarity complex component 2 (LLGL2) as a factor that antagonizes the effects of overexpressed C-P4HAs on HNSC. Silencing of LLGL2 in the human oral squamous cell line Cal-27 upregulates the expression of occludin and increases cancer cell invasion and migration. In contrast, knocking down C-P4HA alone inhibits cell migration and invasion. Furthermore, simultaneously downregulating three C-P4HAs has more pronounced effects on inhibiting cell migration and invasion. Accordingly, high LLGL2 expression is also a marker indicating improved prognosis in patients with HNSC. These results suggest that the interplay between LLGL2 and C-P4HAs may be targeted to mitigate HNSC tumorigenesis and progression. <?Pub Caret 31?>